Estimate of a D region ionospheric electron density profile from MF radio wave observations by the S‐310‐37 rocket. Issue 1 (25th January 2016) - Ashihara, Y.; Ishisaka, K.; Miyake, T.
Abstract: The S‐310‐37 rocket, launched at 11:20 (JST) on 16 January 2007, was equipped with a radio receiver to observe the medium‐frequency (MF) radio wave propagation characteristics in the ionosphere. The radio receiver measured the intensity and the waveform of the radio wave at 873 kHz from the NHK Kumamoto broadcasting station. The polarized mode waves' intensity characteristics were obtained by analyzing the observed waveform. In this study, the S‐310‐37 rocket‐observed polarized mode waves' propagation characteristics are analyzed in order to estimate the electron density profile in the ionospheric D region. These observations become better measurement approach because the electron density profile in the ionospheric D region is difficult to be observed by other equipment such as a Langmuir probe. A Langmuir probe can measure in the ionospheric D region; however, the absolute values may be off by the influence of wake effects around the sounding rocket. It is demonstrated that the propagation characteristics of the polarized mode waves can be successfully used to derive the electron density profile in the ionospheric D region. Key Points: Observed the MF radio wave propagation characteristics in the ionospheric D region The polarized mode waves' propagation characteristics obtained by analyzing the observed waveform Estimated the electron density profile in the ionosphere from the wave propagation characteristics